Robotics and inclusion of students with disabilities in special education (Research, Society and Development, 2021)
The concept of inclusion and inclusive education for children and adolescents with disabilities has been a topic of research for many countries over the last decades. Among the different methods and practices that have been implemented for interventions, the use of novel technologies and especially educational robotics has been proven to be a valuable tool. In this study, the authors attempted to define and examine those skills that are acquired through robotic interventions, and also the way they are associated with successful inclusion. The areas of social, cognitive, and functional skills of children and adolescents with disabilities were examined and their enhancement through robotics was assessed. For the purposes of this review, the authors searched Research Gate, Google Scholar, Scopus, PubMed, and Science Direct and identified relevant research papers. After the application of eligibility criteria, 12 research papers were considered suitable for analysis. The analysis of results indicates that most children and adolescents with disabilities that participated in interventions with robots managed to develop their social, cognitive, and functional skills and in some cases, their inclusion in educational settings was facilitated. The findings of this review support the need for implementation of these newly introduced practices and also some implications are discussed.